LOGISTICAL CHALLENGES AND THE PERCEIVED IMPACT ON THE OPERATIONAL PERFORMANCE OF SELECTED MEDIUM ENTERPRISES IN CAVITE - Berico, Mary Grace; Mendoza, Aaron George; Kang, Jioh; Nabos, Bianca Angela Mae; Nave, Rheanon Kenn (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This study aims to identify the logistics challenges and the perceived level of impact on the operational performance of medium enterprises in Cavite. It specifically focuses on medium manufacturing enterprises located in the City of Dasmariñas, Cavite. A descriptive research design was employed to analyze the participants’ profiles and assess the perceived impact of various logistical challenges. Out of 23 medium manufacturing enterprises in the city, seven agreed to participate, with a total of 107 managers and supervisors who responded to the survey questionnaire. The findings revealed that the primary logistics challenges include software glitches and insufficient data backups in terms of technological factors, rising fuel prices pertaining to external factors, and unsafe working conditions relating to internal factors. Among these, technological building blocks were perceived to have the highest-level impact on the operational performance of the enterprises. The study concluded that technological issues were perceived by participants to have the most significant impact on logistics operations, underscoring the vital role of modern technology in maintaining efficiency and competitiveness. The results further suggest that many medium-sized enterprises still lack the technological resources and modernization necessary to sustain operational performance. It is therefore recommended that medium enterprises invest in upgrading outdated equipment, enhancing technological systems, and implementing regular data backup procedures to minimize disruptions. To obtain a more thorough understanding of logistics performance among medium enterprises, future research is also encouraged to investigate logistics challenges beyond internal, external, and technological aspects. Additionally, a wider range of participants from different industries and geographic areas should be included.